Affordances of a digital library as a publishing medium in a project-based learning environment : the Coredev approach - Abrizah, Abdullah; Zainab, Awang Ngah (Malaysian Educational Technology Association, 2004)
Project-based teaching methods are increasingly used in Malaysian secondary school classrooms with the expectations that students will be engaged by the chance to use different information sources creatively and will especially benefit from the use of various presentation types to improve learning. But the challenges of conducting research project independently are considerable. In project-based learning students formulate authentic, meaningful questions, plan tasks, gather resources and information, evaluate information, collaborate with others, and report findings. To support students in these types of activities, students need a full compliment of tools designed to meet the unique needs of learners. This paper examines the affordances that a digital library can bring to bear on supporting students in these activities. In this paper, we identify some of the reasons why a digital library for school projects, built in a collaborative basis, is needed in project-based education at the secondary school levels. The collaborative environment would provide the platform for the educational community to participate in e-publishing of resources that can be shared by others. In the implementation of this project, the use of the digital libraries would be an integral part of classroom activities. Students should be enabled to publish their own documents in the digital library and share them with others. In this case, students should be allowed to create and submit their project report in the electronic format. Teachers would be given the opportunity to utilize their ICT knowledge by validating the quality of submissions to maintain content quality of the digital library, grade projects online, and add links to other useful resources found in the Internet. A special feature in the digital library that allows the generation and submission of project report is highlighted. Some preliminary research findings regarding studentsâ reception of the digital library and their willingness to publish in the digital library are presented.